Per Jacobsson Lecture : Central Banking in the Crisis: Conceptual Convergence and Open Questions on Unconventional Monetary Policy. (per Jacobson lecture, 2014)
Since the grave disruption of the subprime market at the start of the global financial crisis triggered major turbulences in the functioning of money markets in all large advanced economies, central bankers have experienced extraordinarily demanding and difficult times, characterized by a succession of shocks unseen, in the advanced economies, since World War II. Given the structurally very different economies that central banks were dealing with, one could have expected that the shock of the crisis would have accentuated their differences and given rise to an even more diverse setof central bank policies, conceptual references, and measures in a selfish, inward-looking mode. Instead, however, a phenomenon of 'practical and conceptual rapprochement' took place between central banks, amidst the economic and financial turmoil, with the closest central bank cooperation ever, as symbolically illustrated by the coordinated decrease of interest rates in October 2008. The crisis also started or accelerated a multidimensional process of convergence of key elements of monetary policy thinking and policymaking-'conceptual convergence'-that is far from being achieved, but calls for great attention from both academia and policymakers. This Per Jacobsson Lecture concentrates on this convergence process, reflecting as well on some theoretical and practical issues that are associated with unconventional monetary policy liquidity and quantitative measures and the forward guidance generalization, themselves part of the conceptual convergence phenomenon.